PENGAWASAN IZIN PERGUDANGAN OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN (DISPERINDAG) KOTA PEKANBARU - Nora Oktavia; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The increase in the trade central in the Pekanbaru city makes the more companies or individuals who need the storage of goods, which is the warehouse. So a lot of the warehouses are located in Pekanbaru city don’t have the list of the warehouse. Therefore it is necessary to control by the department of industry and trade in the Pekanbaru city. Controlling is irregularity to the illegal storage stuff can be overcome. The study aims to warehouse in the pekanbaru city, at the planning and managed properly so that increasing net income in the Pekanbaru city.The research is used by the qualitative. This research is using the theory of controlling by mindo Manulang to the decided the standard, to assessment, improve the action. This research techniques are the observation, interview, and the documentation by using technical analyze is descriptive set of qualitative.In the research controlling conducted by the department of industry and trade in the Pekanbaru city is not quite optimal. The second is the lack of coordination between the integrated one-stop service and capital investment in the Pekanbaru city in the late delivery of the list data of the warehouse to the department of industry and trade. The third is still a lack of information to the owner of the warehouse. And the fourth is still a lack of the awareness and knowledge of the warehouse on the warehouse rules.The key word : Controlling, licence, warehouse.